Investigation and applications of all-fiber brillouin ring resonator lasers - Kalli, Kyriacos; Jackson, David A. (My University, 1995)
We examine the theoretical and experimental behavior of Brillouin ring resonator lasers (BRRL), highlighting differences between Brillouin scattering in ring resonators and long fiber lengths. The theory, which assumes that the nonlinear interaction is well-described by two coupled equations for the optical waves, agrees well with measured data. We examine the single and multimode behavior of BRRL and show how this may be usefully implemented in microwave signal generation, in Stimulated Brillouin Scattering gain studies, and to realize a new form of all-fiber frequency shifter.
Keywords: Brillouin scattering; Fiber optics; Lasers Resonators; Wave guides